Los medios de comunicación y su utilización como agentes de socialización en el proceso educativo - Calpa Cachiguango, Andrea Elizabeth (2020)
This research project was carried out at the "Gustavo Iturralde" school to improve the learning process through the media as methodological strategies in which they contribute to the media's correct use in the teaching-learning process. Reason for the quality of the elementary education students of the "Gustavo Iturralde" school, it is evident that they do not know some media and therefore limited to the children in their teaching-learning process. The research's methodological design was framed in the quantitative approach, also called positivist, with the help of the deductive method in which the two variables, cause, and effect, will be evidenced, in which we will statistically identify the facts. Through the application of the observation technique, which will be carried out through a careful examination that the teacher performs on the subjects to be investigated in this case, the students and as an instrument the observation guide since it is a record that evaluates the performances in which allows the teacher to observe the activity developed by the student comprehensively. In this context, it is essential to determine the importance of using the media in the teachinglearning process for students, strengthening their knowledge, and having the right school environment. The research will not be experimental because we are not going to change the theory.